Familial Adenomatous Polyposis—Rendering a Diagnosis Based on Recognition of an Unusual Primary Thyroid Neoplasm - David F. Schaeffer; Eric M. Yoshida; David A. Owen; Kenneth W. Berean (Case Reports in Medicine)
It has been well established in the literature that the cribriform-morular variant of papillary thyroid carcinoma (CMVPTC) has been observed with higher frequency in familial adenomatous polyposis (FAP) patients. In the usual setting, patients with FAP are identified based on their germline mutations and the diagnosis of thyroid neoplasm is made after the FAP diagnosis. We herein report a case in which the recognition of a CMVPTC led to the initial diagnosis of FAP. The histological and clinical features of CMVPTC are reviewed with emphasis on its relationship to FAP.